Organization of visual cortex in the northern quoll, Dasyurus hallucatus: evidence for a homologue of the second visual area in marsupials. - Rosa, MG; Krubitzer, L; Molnár, Z; Nelson, J (1999)
Two visual areas, V1 and V2 (first and second visual areas), appear to be present in the posterior neocortex of all eutherian mammals investigated so far. However, previous studies have not established whether an area homologous to V2 also exists in metatherian mammals (marsupials). Using electrophysiological techniques, we mapped the visual receptive fields of neurons in the striate and peristriate cortices of the northern quoll, an Australian marsupial. We found that neurons in a 2-mm-wide strip of cortex rostrolateral to V1 form a single, relatively simple representation of the complete contralateral hemifield. This area resembles V2 of eutherians in several respects: (i) neurons in the medial half of the peristriate area represent the lower visual quadrant, whereas those in the lateral half represent the upper visual quadrant; (ii) the vertical meridian of the visual field is represented adjacent to V1, while the visual field periphery is represented along the lateral and rostrolateral borders of the peristriate area; (iii) there is a marked anisotropy in the representation, with a larger magnification factor parallel to the V1 border than perpendicular to this border; and (iv) receptive fields of multiunit clusters in the peristriate cortex are much larger than those of cells in V1 at comparable eccentricities. The cortex immediately rostral and lateral to V2 did not respond to visual stimulation under our recording conditions. These results suggest that V1 and V2 together form a 'core' of homologous visual areas, likely to exist in all therian mammals.